(untitled) (RIAF. International Journal of Physical Activity, 2024)
Hip fractures are a cause of disability and morbidity in the elderly population, is defined as the loss of the continuity solution of the bone tissue of the regions of the head, femoral neck, and region intertrochanteric. They are classified as intracapsular and extracapsular. It is important to distinguish them by the impact on the irrigation of the femoral head. The clinical presentation includes groin pain and inability to bear weight on the affected limb, pain may radiate to the distal femur. Physical examination may include observe shortening and external rotation of the affected limb. The present research reveals the role of health professionals in compliance with the principles of the medical ethics in the daily actions of the Rehabilitation specialty in patients with hip fracture.